2017
DOI: 10.1177/1071100717731853
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcomes of a Fixed-Bearing Total Ankle Arthroplasty With Deformity Analysis

Abstract: Level III, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 30 publications
3
28
2
Order By: Relevance
“…Seven studies scored no stars for the item “outcome of interest,” 14,15,31,32,34,37,38 6 studies scored no stars for the item “comparability of cohorts,” 4,14,20,31,37,38 and 3 studies scored 1 of 2 stars for this item. 13,15,34 For the other items of the checklist, where a maximum of 1 star could be obtained, 2 studies did not obtain a star. One study received no star for the item “representativeness,” 34 and the other study received no star for the item “long enough follow-up.” 14…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies scored no stars for the item “outcome of interest,” 14,15,31,32,34,37,38 6 studies scored no stars for the item “comparability of cohorts,” 4,14,20,31,37,38 and 3 studies scored 1 of 2 stars for this item. 13,15,34 For the other items of the checklist, where a maximum of 1 star could be obtained, 2 studies did not obtain a star. One study received no star for the item “representativeness,” 34 and the other study received no star for the item “long enough follow-up.” 14…”
Section: Resultsmentioning
confidence: 99%
“…Case series of MB-TAR and FB-TAR suggest favorable outcomes for both implant types. 3,4,6,9,11,13,18,21,26 Current FB-TAR designs, including the Salto Talaris, only gained traction over the past decade, prompted by the FDA’s restriction on MB-TAR in the United States. By the time the STAR was introduced to the US market in 2009, FB-TAR was established an alternative to MB-TAR.…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively high reoperation rates in both groups, but most address impingement or cyst formation without the need to remove the metal implants. 3,4,6,9,11,14,21 Case series are important in understanding anticipated outcomes of both designs but fail to compare MB-TAR and FB-TAR with a high level of evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our decision to include multiple different implant systems in the present study stems from the fact that all 4 implant systems have had good results reported in the recent literature, with midterm survival rates higher than 90%. 6,9,13,18,30 Both mobile- and fixed-bearing implants were included because no study has shown a difference between the two in terms of survival rates or outcomes. By including multiple different implant systems and multiple surgeons, we felt that our findings on predictors of failure would be more generalizable.…”
Section: Discussionmentioning
confidence: 99%